Development of a mathematical model of transportation problem with limited time - Makovetska, Svetlana; Seidykh, Olga (My University, 2016)
This work is dedicated to the development of a mathematical model of the transport problem solution (TS) with a time limit.
Keywords: mathematical model; transport task; математичні моделі; транспортні задачі; математические модели; транспортные задачи; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки